Colonização e dispersão nos sítios de ocorrência, a genética das populações e história natural de Partamona ailyae Camargo, 1980 (Hymenoptera: Apidae: Meliponini) - Cardoso, Pedro Filipe Menezes (Universidade Federal de São Carlos, 2016)
Particular biological features of different bee groups can affect how a certain area will be occupied by them and this can affect directly the genetics of their populations over the long term. In Brazil, there are few studies about gene variation and genetic structure of bee natural populations, as well as on the genetic differentiation levels between eusocial bee populations. The Partamona genus comprises 33 species, distributed from Southern Mexico to Southern Brazil. Partamona ailyae, the model species of this study, occurs in rainforests of Southwestern Amazonia, Central Brazil and xeric regions of Piauí. Its wide distribution, as well as the ability to occupy such heterogeneous environments, piqued our interest to take P. ailyae as a study model. This work aimed to analyze the occupation process at the P. ailyae occurrence sites, population genetics and interpopulational gene flow, and the natural history of this species. Eight expeditions were carried out, and 41 localities of 10 states of Brazil were visited. Among them, active colonies of P. ailyae were found only in 17 localities, being collected specimens of 75 nests. To identify the mitochondrial lineages present in the sampled colonies, five gene regions were used (COI, CytB, 12S, 16S and COI-COII). Estimates of polymorphism levels showed COI and CytB as the most variable regions (11 and seven haplotypes, respectively). For the ribosomal genes, only a few samples were analyzed, because few differences were identified among the sequences. All the 31 samples analyzed for the 12S showed a five bases insertion starting from the position 25 of the sequence, a result not observed in other Partamona species. The most informative genes (COI and CytB) had their sequences concatenated (1114pb). For these regions, 13 haplotypes were observed, two of them were shared and 11 characterized as exclusive of localities. The AMOVA showed that 94.3% of the gene variation is due to interpopulacional differences, revealing a high differentiation among the populations (ΦST = 0.9426; P = 0.000). In addition, one individual from each colony was analyzed for eight heterologous microsatellite loci designed from Melipona bicolor and Partamona helleri. A moderate and statistically significant XIV interpopulational genetic differentiation (ΦST = 0.1491; P = 0.000) was found. The cluster analysis identified four groups by ΔK as the ideal model, and STRUCTURE software showed that all individuals could belong to more than one group, corroborating the “Assignment test”, which indicated that only 50% of the samples were correctly assigned to their original population. Phenotypic segregation analysis was realized in some offsprings, revealing a monoginic/monandric familial structure. From the mitochondrial data, the Mantel test showed a significant correlation between genetic distance and geographic distance (r = 0.2589; P = 0.0231), whereas on basis of the nuclear data, the Mantel test did not indicate significant correlation between genetic distance and geographic distance (r = 0.2090; P = 0.0610). Fu’s Fs and R2 tests did not show significant values. The Bayesian Skyline Plot analysis (BSP) did not show significant fluctuations in the effective size populations of P. ailyae, indicating population stability over time. The values of ΦST estimated for mitochondrial genes and microsatellites were compared, being detected evidence of sex-asymmetric dispersal, in which females are responsible for the areas occupation, and males constitute the disperser sex. In addition, some relevant aspects of the natural history of P. ailyae are shown.
Keywords: Abelhas sem ferrão; Colonização; Estrutura genética; Diferenciação populacional; Marcadores moleculares; Stingless bees; Colonization; Genetic structure; Population differentiation; Molecular markers; OUTROS